Traditional Music Based Cultural Tourism: An Opportunity for Revitalization and Empowerment of Local Communities through Talempong - Rina Armeniza Aziz; John JOI Ihalauw; Sugiarto Sugiarto (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Talempong, a Minangkabau bronze gong ensemble in West Sumatra, embodies both cultural identity and creative economic potential, yet its role in cultural tourism remains rarely studied. This study examines Talempong's potential as a tourism attraction and creative economy instrument, as well as a strategy for revitalization and community empowerment. Using a qualitative case study approach through interviews, participant observation, and documentary analysis, data were triangulated and analyzed using the interactive model of Miles, Huberman, and Saldana. Findings indicate that Talempong functions as a living heritage asset, a performative tourism product, and a revenue-generating creative good through instrument making, performances, music education, and souvenirs, yet faces challenges of generational transmission, limited market access, and weak institutional support. Discussions highlight that the success of Talempong-based tourism depends on the synergy of cultural authenticity, community involvement, and market packaging. The study concludes that collaborative governance between artisans, the village, and the creative sector can revitalize Talempong while strengthening community livelihoods, with practical implications for sustainable music tourism policy.